LINGUISTIC-PRAGMATIC ANALYSIS OF ENGLISH AND UZBEK CULTURAL REALIA IN LITERARY TEXTS AND INNOVATIVE SOLUTIONS FOR THEIR TRANSLATION (KONFERENSIYA, 2026)
This paper is dedicated to a comparative linguistic-pragmatic analysis of linguocultural realia found in English and Uzbek literary texts (fiction). The study aims to investigate the peculiarities of interpreting realia during translation, focusing on how these terms fulfill aesthetic and stylistic functions within a narrative. It examines the lexical and pragmatic problems arising from the translation of these elements, emphasizing strategies like transcription, descriptive translation, and contextual compensation required to preserve the local color and authentic cultural significance of the source text.